Correlation of matrix metalloproteinase-2 and -9 expression with recurrences in primary spontaneous pneumothorax patients - Chiu, Wen-Chin; Lee, Yi-Chen; Su, Yu-Han; Chai, Chee-Yin; Hu, Stephen Chu-Sung; Yuan, Shyng-Shiou F.; Chou, Shah-Hwa (Journal of Thoracic Disease, 2016)
Background: Primary spontaneous pneumothorax (PSP) is a common benign disorder. However, unpredictable recurrence is a major concern for most patients. The aim of the present study was to assess the role of matrix metalloproteinase-2 (MMP-2) and MMP-9 in alveolar macrophages of patients with PSP and its relationship with recurrence. Methods: Ninety-two patients who received needlescopic video-assisted thoracoscopic surgery (NVATS) wedge resection of lung with identifiable blebs for PSP were enrolled for the study. Immunohistochemistry was performed to evaluate the expression of MMP-2 and MMP-9 in lung tissues of patients with PSP. The result was correlated with clinicopathological variables and recurrence rates by the chi-square test. The value of MMP-2 and MMP-9 for overall recurrence was evaluated by univariate and multivariable Cox regression analyses. Results: The MMP-2 and MMP-9 staining was predominantly observed in alveolar macrophages of patients with PSP. We found that MMP-2 (recurrence: P